On the Medialization of the World and the Mediatization of Discourse - Theo Hug; Rainer Leschke (Media Theory, 2021)
Descriptions and analyses in both media studies and communication studies correspond to a broad spectrum of terms, descriptive modalities, and ways of thematization. These terminologies and perspectives are partly overlapping but also distinct as regards histories and preferences in various academic contexts. Some expressions also serve as guiding metaphors, generic terms or catchwords with programmatic or paradigmatic claims. Medialization and mediatization are among these expressions that have achieved a high degree of popularity especially in German scholarly discourse. In this paper, we first examine some aspects of the politics of concepts of corresponding discourses in German media and communication studies. In contrast to synonymous or all-inclusive uses of the terms, we argue for a conceptual differentiation and constructive coexistence that can prove fruitful for both theoretical and empirical research.